Knowledge of Medical University Students over Osteoporosis - Enteshari-moghaddam, Afsaneh; Zakeri, Anahita; Atalu, Abolfazl; Abbasi, Vahid (Archives of Advances in Biosciences, 2019)
Introduction: Osteoporosis is called “silent illness", in which the bones get lost without any signs , with symptoms of pain and fracture developing in advanced stages . According to the World Health Organization statistics, about 40% of women and 10% of men are at risk of osteoporosis during their lifetime. Osteoporosis is more common among women than in men and in Iran half of women over the age of 45 and 90% of women over 75 are afflicted with it. The aim of this study was to assess the knowledge of Ardabil medical university students toward osteoporosis. Materials and Methods: This is a descriptive cross-sectional study that has been performed over 258 students of Ardabil medical university in different fields of study. The data collection method was a research based questionnaire including demographic data and questions about knowledge of osteoporosis. Data were analyzed using statistical methods in SPSS version 16. P value of less than 5% was considered as significant. Results: 69.5 percent of students were female students and the rest were male. 31.2 percent had good knowledge, 61.3 percent average knowledge and 7.5 percent poor knowledge toward osteoporosis. The most correct answer was “to have suitable nutrition in preventing osteoporosis” and “high risk to older people for osteoporosis” which were statistically significant and the lowest correct answer (5.8%) was related to “increase the risk of osteoporosis by removing ovaries”. Conclusion: Considering the high prevalence of osteoporosis and increasing the number of seniors over the past decades, the country should take necessary measures in order to raise the level of awareness of the community and especially students about osteoporosis such as the risk factors, prevention and complications of the disease through the health system and governmental or non-governmental organs .